Celebrating the Career of W. Warner Burke: The Very Model of an OD Scientist-Practitioner. (December 2020) - Church, Allan H.; Pasmore, William
The purpose of this special issue is to recognize and reflect on the contributions and legacy of scientist-practitioner W. Warner Burke. Burke's many contributions to the theory and practice of organization development over the past six decades have had both a foundational and evolutionary impact on the field. This special issue presents seven articles that reflect various facets of his contribution as a colleague, scholar, practitioner, and mentor.